Observed range dynamics of South African amphibians under conditions of global change. (7th January 2015) - Botts, Emily A.; Erasmus, Barend F. N.; Alexander, Graham J.
Abstract Changes in the size and location of species ranges are a recognized response to environmental changes. We assessed recent range dynamics of South African amphibians using data consolidated by the South African Frog Atlas Project, which provided both historical (1905–1995) and recent distribution data (1996–2003). Sampling differences were accounted for using a correction factor and subsampling protocols. Changes to the size of species ranges and shifts in the mean range centre for latitude, longitude and altitude were assessed. Most (70%) of the assessed species showed range contractions. Of the expected climate change predictions, only upslope shifts were supported (mean 47.6 m). There were no significant mean latitudinal shifts for the assessed group of species. Species of the Bushveld region shifted northwesterly and upslope, while species of the Winter Rainfall region also shifted northwesterly. The small, though significant, general taxon‐wide trends where minor in comparison to the wide variety of idiosyncratic, species‐specific range changes that were observed. The species‐specific observed range changes that were documented should be used to further investigate range change drivers on an individual species basis.